A study on informal learning spaces in the faculty of cognitive sciences and human development (FCSHD) - Fatimah, Binti Mohamad Zin (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The aim of this study is to investigate the relationship between usage of informal learning spaces and student engagement in learning. At the same time, this study also investigates students' choice, requirement and preference in the informal learning spaces. This research was conducted in one of the faculty in University Malaysia of Sarawak (UNIMAS) which is Faculty of Cognitive Science and Human Development (FCSHD) where informal learning spaces are provided. This is a quantitative study involving second and third year student in FCSHD who have knowledge and experience about four types of informal learning spaces in FCSHD: rest room, resource room, lounge and computer lab. A set of questionnaires constructed from previous research findings about informal learning spaces is used as the research instrument. There are 60 sets of questionnaires distributed to the respondents from two programme in FCSHD which are Cognitive Sciences and Human Development. The descriptive statistic is used to find the popular aspect in each informal learning space, the reason why students use informal learning spaces, and student preference in each informal learning space. It is also used to analyze the aspect in the spaces that can be improved in order to facilitate student to enhance informal learning processes and increase student engagement. While inferential statistic is used to test research hypotheses by using Correlation-Pearson test. This study found that there is a relationship between usage of informal learning spaces and student engagement in learning. Moreover, it also found that student choice, requirement and preference in the informal learning spaces depend on the environment and facilities provided in the spaces. It can be concluded that well-designed informal learning spaces can encourage students to use the space and increase student engagement in learning.